Wireless Sensor Networks 8th European Conference, EWSN 2011, Bonn, Germany, February 23-25, 2011, Proceedings - Marrón, Pedro José; Whitehouse, Kamin (Computer Communication Networks and Telecommunications,, 2011)
This book constitutes the refereed proceedings of the 8th European Conference on Wireless Sensor Networks, EWSN 2011, held in Bonn, Germany, in February 2011. The 14 revised full papers presented were carefully reviewed and selected from 87 submissions. The papers are organized in topical sections on routing and mobility, optimization techniques, MAC protocols, algorithms, and systems and abstractions.